Consensus guidelines for the management of primary central nervous system lymphoma for low and middle-income countries - Hafiza Fatima Aziz; Saqib Kamran Bakhshi; Noman Ahmed; Mohammad Hamza Bajwa; Adnan Abdul Jabbar; Asim Hafiz; Ahmed Gilani; Muhammad Usman Khalid; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement); Syed Ather Enam (Journal of the Pakistan Medical Association, 2024)
Primary lymphoma of the central nervous system (PCNSL) is a rare and aggressive form of extranodal non-Hodgkin lymphoma primarily involving the brain, spinal cord, cerebrospinal fluid, and eyes. The role of surgical intervention in PCNSL is currently limited to biopsy and decompression of critical structures if needed – extended resection is debated. Chemotherapy is the mainstay of treatment. In lower and middle-income countries (LMICs), issues like delayed diagnosis and resource constraints are widespread. These guidelines provide a framework for addressing PCNSL in LMICs, emphasizing the importance of early diagnosis, tailored treatment approaches, and ongoing patient monitoring to improve outcomes for this rare and aggressive disease. Keywords: Lymphoma, non-Hodgkin, biopsy, nervous system, physiologic decompression, spinal cord, brain tumours